Neither carrots nor sticks?: Challenges surrounding data sharing from the perspective of research funding agencies : a qualitative expert interview study [interview excerpts] - Anger, Michael; Wendelborn, Christian; Winkler, Eva C.; Schickhardt, Christoph (Universität, 2022)
This dataset contains summaries from interviews with data sharing experts from internationa funding agencies on their organisation's data sharing p...